Dominant point defects in doped cadmium telluride CdTe:Ge - Freik, D.M.; Pysklynets, U.M.; Mezhylovska, L.Y. (Functional Materials, 2007)
Quasi-chemical equations have been proposed for the formation of point defects (PD) and complexes thereof in germanium-doped cadmium telluride single crystals. Baric and temperature dependences of dominant PD and free charge carriers concentrations in CdTe:Ge have been obtained. Equilibrium constants for quasi-chemical equations of complex (GeCd⁺VCd²⁻)⁻ formation have been determined as well as those for germanium transition from cation to anion sublattice of the main matrix. Results of the investigation have been explained by restricted solubility of the dopant under high temperature equilibrium of the PD. Dependence of germanium solubility in CdTe upon temperature and partial pressure of cadmium vapor have been calculated theoretically.